(3ebOeI aj GdJNWjW GdJfehj GdEbdjejs - (3YKeGf eMeO(B, (3Zfjes ((3YeGf(B:s (3OGQ UaGA ddfTQ hGdJhRjY(B,s, 1999)
(3eTcdI GdJNda(B- (3GdJNWjW GdJfehj(B- (3GdJNWjW GdEbdjej(B((3GdfTCI hGdHOGjI(B)- (3GdJNWjW GdEbdjej(B((3Gdeaghe hGdGSGdjH hGdNUGFU(B- (3GdJSdSd GdeQMdj hGdELQGFj dYedjI GdJNWjW GdEbdjej(B- (3fXQjI GdJNWjW GdEbdjej(B- (3GdJLQHI GdCQOfjI(B.s
Keywords: (3GdJNWjW GdJfehjs; (3GdJfejI GdEbJUGOjIs; (3GdJfejI GdEbdjejIs